Impact of visual means on the development of coherent speech of senior preschoolers - Портян, М. О.; Головченко, Н. П. (Scientific notes of the pedagogical department, 2019)
The ar cle deals with the issue of the development of senior preschoolers’ coherent speech through the use of visual means of teaching. It is determined that the eﬀec ve method of development of senior preschoolers’ coherent speech is visual simula on. Due to this method, the children of this category form a logical, consecu ve expression of their own thoughts, children develop their vocabulary, syntac c and lexico-gramma cal language, sound-component analysis and synthesis, which contributes to competent speech expression. The course of the experimental methodology for the development of senior preschoolers’ coherent speech is highlighted by means of visibility. To iden fy the ini al level of the forma on of coherent speech of children, we selected four tasks for the survey, which, in our opinion, most fully reveal the depth of development of coherent speech preschoolers: drawing up proposals for individual «situa onal pictures» (ac on pictures); drawing up a sentence in three pictures related by meaning; transla on of the text (a familiar tale or a short story) drawing up a story from a picture or a series of plot pictures. As a result of the study, it was proved that visual teaching means (situa onal plot pictures, ac on pictures, graphic picture diagrams, mnemonics) using the visual simula on method (scale modeling) contribute to the crea ve development and improvement of the various language abili es of children, par cularly the children of the senior preschool age. The proposed experimental methods proved to be eﬀec ve in the developing coherent speech for preschoolers, because children acquired the ability to consistently, meaningfully and logically express their posi on, developed communica on skills due to the expansion of vocabulary, syntac c and lexico-gramma cal structure of speech. Prospects for further research are seen in the search and selec on of various methods for the development of coherent speech, for senior preschool children, but also for children of other ages, not only by means of visualiza on, but also through speech-game ac vity, toys, logorhythmics, works of art (stories, tales) and suchlike.